The Influence of Corporate Social Responsibility on Company Performance in the Chemical Industry Sector - Nugraha, Daffa Widyan; Imronudin, I (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to analyze the impact of various independent variables, namely Corporate Social Responsibility (CSR), company size, leverage, and board size, on company performance measured by the Tobin's Q ratio as the dependent variable. The sampling technique used was Purposive Sampling resulting 70 sample data for 4 year observating from 2019-2022. The data was analyzed using multiple regression, since the data in the study was pooled data, Chow test was conducted to choice the best model. Based on the Hausman test, fixed effects model was elected. The result showed that CSR and company size have a negative effect on the Tobin's Q ratio, while leverage and board size do not show significant impact. The study recommends that companies in the chemical industry sector carefully design CSR programs to ensure that these programs genuinely reflect their commitment to sustainability and social responsibility, as improper implementation can reduce company value. Additionally, companies are advised to reevaluate their organizational size to find an optimal balance that can support financial performance. The study also suggests that the government should strengthen regulations that support responsible and sustainable business practices, and provide incentives for companies that implement environmentally friendly practices. Improved transparency and reporting on CSR are also considered important to provide accurate information to the public and other stakeholders.